The Relationship Between Interest in Learning and Critical Thinking Skills of Junior High Students in Science Learning - Ersa Ramadani; Frelyana Tiro; Haeruddin Haeruddin; Mohammad Jamhari; Afadil Afadil (Universitas Tadulako, 2025)
This study aims to determine the relationship between interest (X1) and critical thinking skills of seventh-grade students in science learning at SMP Negeri 4 Tanantovea. This study is a descriptive correlational study. The research sample was selected using total sampling, comprising all seventh-grade students from two classes, totalling 36 students. The instruments used in this study were a questionnaire on students' interest in learning and a critical thinking test. The questionnaire on interest in learning and the critical thinking test were subjected to content and construct validity tests. A field trial was conducted with 36 students, comprising 19 female and 17 male students. The instruments used in this study were a critical thinking test and a questionnaire on students' learning interests. The questionnaire on learning interest consisted of 20 statements, while the critical thinking test consisted of 10 essay questions. All instruments underwent content validity testing by experts, empirical validity testing using Pearson product-moment correlation, and reliability testing using Cronbach's Alpha. Prerequisite tests were conducted using the Shapiro-Wilk normality and linearity tests with SPSS 22 software. The study results in Grade VII of junior high school concluded a relationship between interest and critical thinking ability, with a correlation value of 0.402 and a regression equation of Ŷ = Y = 57.813 + 0.165X1. Furthermore, based on the calculated r value of 0.442, the criteria for the strength of the relationship between the variables of interest and critical thinking indicate a fairly strong relationship.